lựa chọn một số bài tập bổ trợ nhằm tăng hiệu quả thực hiện kỹ thuật phát bóng cao tay chính diện cho sinh viên trường Đại học Mỏ- Địa chất - Tôn, Thanh Hải (Thiết bị giáo dục, 2023)
Abstract: By using scientific research methods, the author has given supplementary exercises to increase the efficiency of high-hand kicking technique for students of the University of Mining and Geology